Analisis Dan Perancangan Sistem Informasi Pada Aplikasi Lazada - Ale Mahesa; I Made Ardian Givari; I Putu Eka Dharma Wijaya; I Putu Eka Indrayana (Primakara University, 2022)
Along with the development of information technology, human work, especially in obtaining information becomes easier. Not only in obtaining information but also in processing information into data that humans need. The convenience of internet provider tariff services along with the affordability of the hardware that supports it also contributes to supporting the delivery and acquisition of information through internet media. The design of a web- based sales system is a system that aims to promote, market, as well as support the purchasing power and competitiveness of the company in reaching its consumers online. With the website, it is hoped that the existing information can reach consumers with a wider coverage area because the internet is a promotional media that is easy and fast to access. The data used in the preparation of this final project include primary data and secondary data. The research method used is field study and literature study. Field studies include observations, interviews, and documentation. While the literature study is carried out by conducting research on the results of the literature related to the problem, the data obtained is then analyzed more deeply, including problem analysis, needs analysis, hardware, software, and cost analysis. System design includes data flow design, data dictionary, erd, normalization, table relations, database structure design and input output design.